The Relationship Between Moral Development and Obedience Students on School Regulations At Khaira Ummah Islamic Middle School Padang City - Fauzana Elvira; MHD Natsir (Universitas Negeri Padang, 2023)
This research was motivated by the low level of student compliance with school regulations at Khaira Ummah Islamic Middle School, Padang City. This is thought to be due to the failure to achieve the objective indicators of the Usrah extracurricular program, which is moral development at Khaira Ummah Islamic Middle School, Padang City. This type of research is correlational using a quantitative approach, the aim is to reveal the relationship between Usrah extracurricular moral development and compliance with school regulations at Khaira Ummah Islamic Middle School, Padang City. The population of this study were all students at Khaira Ummah Islamic Middle School and 50 students were sampled using the Simple Random Sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use percentage formulas and product moment formulas. The results of the research show that Usrah extracurricular moral development and students compliance with school rules are classified as poor and there is a significant relationship between Usrah extracurricular moral development and students' compliance with regulations at Khaira Ummah Islamic Middle School. Research suggestionsKeywords: Moral development, obedience, students